2016
DOI: 10.1209/0295-5075/116/36001
|View full text |Cite
|
Sign up to set email alerts
|

Super-stretchable borophene

Abstract: Recent success in the synthesis of the two-dimensional borophene on silver substrates has attracted strong interest in exploring its extraordinary properties for potential technological applications. The single-layer borophene has a buckled structure with atomic ridges. By using the first-principles density functional theory calculations, we show that the two-dimensional borophene is highly stretchable with strong anisotropy The strain-to-failure in the direction along the atomic ridges is nearly twice as larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…Good agreements are achieved for the three acoustic branches in the long wavelength limit. Similar phonon dispersion can be found from other ab initio calculations262938. There is no imaginary mode from the VFF model, which appears in the ab initio calculations for the flexure mode in the long wave limit26282938.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Good agreements are achieved for the three acoustic branches in the long wavelength limit. Similar phonon dispersion can be found from other ab initio calculations262938. There is no imaginary mode from the VFF model, which appears in the ab initio calculations for the flexure mode in the long wave limit26282938.…”
Section: Resultssupporting
confidence: 82%
“…Free edges in the borophene nanoribbon were found to be important for mechanical, electronic, magnetic, and thermal transport properties343536. The strain effect has been studied for mechanical properties283738, or magnetic properties in borophene39. Several defects were predicted to cause considerable effects on the anisotropic mechanical properties of the borophene30.…”
mentioning
confidence: 99%
“…However, the ZA branch has imaginary frequency along Γ-X direction. Negative frequency means that the restoring forces cannot be generated for the ZA branch 51 .…”
Section: B Optical Properties Of Borophenementioning
confidence: 99%
“…In fact, recent studies have suggested that the tensile strength of borophene is dictated by out-of-plane soft-mode phonon instability under biaxial tension or uniaxial tension along the a direction 52 , and free-standing borophene is instable even under high tensile stress 51 .…”
Section: B Optical Properties Of Borophenementioning
confidence: 99%
“…The following first principles calculations have predicted that striped borophene possesses remarkable mechanical properties 35,36 , which may rival graphene 16 . However, phonon instability in striped borophene is observed 37 , which may challenge previous results demonstrating that borophene is stiffer than graphene along a direction 16,35,36 . striped borophene are evaluated using first principles calculations.…”
Section: Introductionmentioning
confidence: 99%